THE ONE WRITING HABIT THAT TRULY MAKES A DIFFERENCE: REVISING AFTER FEEDBACK - Muhammadova Ferangiz (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This research explores how revising written work after receiving feedback can enhance the writing abilities of learners at the B1 proficiency level. The study integrates both theoretical perspectives and empirical classroom evidence, drawing on data collected through questionnaires, interviews, and samples of students’ compositions. The analysis reveals that learners often struggle with grammatical accuracy and structural coherence; however, the practice of revising texts based on feedback enables them to recognize and address these issues more effectively. Furthermore, the findings indicate that when students actively engage with feedback and practice consciously, they gradually develop greater confidence and produce clearer, more accurate written work.